Consumption Pattern and Nutritional Status Related to Adolescent Dysmenorrhea - Davidson, Sarah Melati; Dampang, Damelya Patricksia; Rombe, Asriani (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Adolescent women will experience puberty which is marked by the occurrence of menstruation. During menstruation, adolescents will experience problems such as menstrual pain or dysmenorrhea. The aim of this study was to determine the relationship between consumption patterns and nutritional status with adolescent dysmenorrhea.Method: This study uses an analytical survey design with a cross sectional approach. Subjects were selected by purposive sampling, namely adolescent girls’ class XI MIPA 1-4, totaling 84 people. Data were analyzed using Pearson's test to determine the significance of the relationship between consumption patterns and nutritional status to adolescent dysmenorrhea.Result: This study showed a significant relationship between nutritional status and the incidence of dysmenorrhea in class XI students at SMA Negeri 2 Toraja Utara (p<0.05; r=0.0224). In addition, this study did not find any relationship between the level of energy and carbohydrate adequacy with the incidence of dysmenorrhea (p>0.05). The results of the statistical test showed r = -0.039, which means that there is a weak relationship in a negative direction between the incidence of dysmenorrhea and the frequency of carbohydrate consumption, and p = 0.726, which means that there is a relationship but not significant. This study also shows the results of statistical tests r = -0.036 and p = 0.743, which means that there is a weak and insignificant relationship between the incidence of dysmenorrhea and the frequency of consumption of caffeine sources.Conclusion: Based on the research that has been done, it can be concluded that the incidence of dysmenorrhea in most respondents is in the moderate level category and the nutritional status of respondents is generally in the normal category.